2014
DOI: 10.1093/rheumatology/keu216
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between changes in cytokines and clinical outcomes for early phase (proof of concept) trials in active diffuse systemic sclerosis using data from an imatinib study

Abstract: http://clinicaltrials.gov/show/NCT01545427.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
2
3
0
Order By: Relevance
“…Although it is still a controversial issue in the literature, some studies have indirectly suggested the potential usefulness of TGF- β 1 levels as a biomarker. This came to light when they evaluated the reduction of TGF- β 1 after specific treatments [18, 19]. Most of the studies have failed to establish a relationship between TGF- β 1 serum levels and clinical features in SSc patients [79] but, in our study, we demonstrated a significant association between higher serum TGF- β 1 levels and diffuse subset, digital ulcers, lung fibrosis, skin involvement, and positive antitopoisomerase I.…”
Section: Discussionsupporting
confidence: 52%
“…Although it is still a controversial issue in the literature, some studies have indirectly suggested the potential usefulness of TGF- β 1 levels as a biomarker. This came to light when they evaluated the reduction of TGF- β 1 after specific treatments [18, 19]. Most of the studies have failed to establish a relationship between TGF- β 1 serum levels and clinical features in SSc patients [79] but, in our study, we demonstrated a significant association between higher serum TGF- β 1 levels and diffuse subset, digital ulcers, lung fibrosis, skin involvement, and positive antitopoisomerase I.…”
Section: Discussionsupporting
confidence: 52%
“…However, also in this situation, the low number of cases does not permit postulating a class-specific immunosuppressant effect. Similar observations have been described for plasma sVCAM-1 concentrations after treatment with imatinib [ 46 ], prostanoids [ 47 ], and nifedipine [ 48 ]. The numerical decline of ANA titers in our study during immunosuppression may additionally indicate a systemic effect on plasma cell activity.…”
Section: Discussionsupporting
confidence: 82%
“…T cells from mice lacking Abl kinases, a molecular target of imatinib and nilotinib, exhibit defective activation in response to T cell receptor stimulation 38 . In a 6-month clinical trial of imatinib for the treatment of dcSSc, Pope, et al found that the change in plasma levels of soluble CD40L was significantly negatively correlated with change in the physician’s global assessment 39 . This suggests that individuals with increased serum CD40L (and multianalyte signatures) may benefit from imatinib and nilotinib treatment.…”
Section: Discussionmentioning
confidence: 99%